2020
DOI: 10.1016/j.apsb.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Miltirone induces cell death in hepatocellular carcinoma cell through GSDME-dependent pyroptosis

Abstract: Pyroptosis is a form of programmed cell death, and recently described as a new molecular mechanism of chemotherapy drugs in the treatment of tumors. Miltirone, a derivative of phenanthrene-quinone isolated from the root of Salvia miltiorrhiza Bunge, has been shown to possess anti-cancer activities. Here, we found that miltirone inhibited the cell viability of either HepG2 or Hepa1-6 cells, and induced the proteolytic cleavage of gasdermin E (GSDME) in each hepatocellular carcinoma (HCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 53 publications
(84 reference statements)
6
96
0
Order By: Relevance
“…Consistently, flow cytometry data showed that depletion of GSDME do not rescue the cell death caused by CBD, but GSDME knockdown cells increase the proportion of Annexin V-PE single-positive cells and reduce the percentage of double-positive cells ( Supplementary Figure 6B ). These data indicated that the deficiency of GSDME may switch CBD-triggered cell death from pyroptosis to apoptosis ( Zhang et al, 2020 ). Previous studies have demonstrated that GSDME-dependent pyroptosis can be activated by pro-apoptotic caspases, such as caspase-3 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, flow cytometry data showed that depletion of GSDME do not rescue the cell death caused by CBD, but GSDME knockdown cells increase the proportion of Annexin V-PE single-positive cells and reduce the percentage of double-positive cells ( Supplementary Figure 6B ). These data indicated that the deficiency of GSDME may switch CBD-triggered cell death from pyroptosis to apoptosis ( Zhang et al, 2020 ). Previous studies have demonstrated that GSDME-dependent pyroptosis can be activated by pro-apoptotic caspases, such as caspase-3 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, recent research has shown that chemotherapy-induced pyroptosis is mediated by the BAK/BAX–caspase-3–GSDME pathway ( Zhang et al, 2018 ), indicating that the pro-apoptotic factors of the BCL-2 family may be involved in cell pyroptosis. Moreover, Zhang et al (2020) have demonstrated that mitochondrial dysfunction triggered caspase3–GSDME pathway activation can eventually lead to pyroptosis in response to Miltirone in HCC cells. There may therefore be a similar mechanism in CBD-induced pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, many studies have indicated that reagents or drugs targeting GSDME showed an antitumor effect. For instance, Miltirone, derived from a traditional herb Salvia miltiorrhiza, was shown to possess antitumor activity by inducing GSDME activation in hepatocellular carcinoma 51 . Furthermore, a PLK1 kinase inhibitor was reported to improve the effect of cisplatin in the treatment of esophageal squamous cell carcinoma by inducing pyroptosis 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Gasdermin proteins have been documented to possess inherent toxic activity of the Gasdermin-N terminal fragments, which are frequently masked by inhibitory Gasdermin-C terminal fragments (19,44,45). Proteolytic cleavage the hinge loop between these terminals to unleash the necrotic Gasdermin-N fragments to squeeze the inner leaflet of membrane and form nanopores with a size of~18 nm in the cellular plasma membrane (44,(46)(47)(48). Physical rupture of pyroptotic cells causes the leakage of inflammatory factors IL-18, IL-1b, and DAMPs to amplify the local and systemic inflammatory response, suggesting the immunogenic potential of pyroptosis (49,50).…”
Section: Discussionmentioning
confidence: 99%